The influence of emotional intelligence on performance in competitive sports: A meta-analytical investigation - Kopp, A.; Jekauc, D. (Sports, 2018)
Emotional intelligence (EI) is considered as a factor influencing sport performance. The research findings are inconsistent with respect to the size and even the direction of the relationship, however. In order to summarise the available evidence, we conducted a meta-analysis examining the relationship between emotional intelligence (EI) and sports performance in competitive sports. A systematic literature search was conducted in June 2018. We identified 21 studies targeting EI and sports performance in competitive sports. We calculated correlation (r) to estimate the effect of the relationship. A random effects model was used to interpret findings. The meta-analysis of 22 effect sizes on the response of 3.431 participants found a small but significant relationship between EI and sports performance (r = 0.16). Additionally, the conceptualisation of EI (ability concept, trait concept, or mixed-model concept), type of publication, citation counts, and publication date turned out not to be significant moderators. Overall, the result is encouraging regarding the value of EI as a possible predictor in sports performance